If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 = -4 + 2(5 + -6v) 90 = -4 + (5 * 2 + -6v * 2) 90 = -4 + (10 + -12v) Combine like terms: -4 + 10 = 6 90 = 6 + -12v Solving 90 = 6 + -12v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '12v' to each side of the equation. 90 + 12v = 6 + -12v + 12v Combine like terms: -12v + 12v = 0 90 + 12v = 6 + 0 90 + 12v = 6 Add '-90' to each side of the equation. 90 + -90 + 12v = 6 + -90 Combine like terms: 90 + -90 = 0 0 + 12v = 6 + -90 12v = 6 + -90 Combine like terms: 6 + -90 = -84 12v = -84 Divide each side by '12'. v = -7 Simplifying v = -7
| 5x-8=-x-4 | | 3=5=x/2 | | f(x)=9x^2+7x+8 | | a^2+a-1+-a-1= | | 2x+22=60 | | 5k^2=5k | | 290688=bc | | -5(5n+4)=-145 | | -6H+3=9 | | 7x+12y=10 | | x=4-2(13) | | 5.6=4.7x-9 | | 7z+1=8z | | 1=2x^2-4x | | -12(x+1)+4(4x-3)=3(x-3)+14 | | 2w/2 | | 10/7h=170 | | 1/3(8x-16)=12 | | 6(x-9)=66 | | 4k^2-6=k^2+17k | | -120=y-47 | | 3(X+5)+3X=8X-X(2)+15.75-13.15 | | -x-2(-x-3)=-4+x | | 0=2x(2)-4x | | 6(4-2y)-1y=-145 | | z-53=798 | | 3x^2+9x-5x+4x^2= | | 501169=bxc | | -1(21k-3+4)-17k= | | 2x-3y=4+5x-3y | | 71407=bxc | | 3(X+5)+3X=8X-X(2) |